Assessment of disease‐related knowledge and possible factors associated with the knowledge level among Chilean patients with inflammatory bowel disease. Issue 11 (20th March 2017) - Simian, Daniela; Flores, Lilian; Quera, Rodrigo; Kronberg, Udo; Ibáñez, Patricio; Figueroa, Carolina; Lubascher, Jaime
Abstract : Aims and objectives: To assess disease‐related knowledge among patients with inflammatory bowel disease and to identify the factors that are possibly associated with the knowledge level. Background: Disease‐related knowledge can positively influence the acceptance of the disease, increase treatment compliance and improve the quality of life in patients with inflammatory bowel disease. Design: An observational, cross‐sectional study was conducted and prospectively included patients from the inflammatory bowel disease programme between October 2014–July 2015. Methods: A Spanish‐translated version of the 24‐item Crohn's and Colitis Knowledge score was used to assess disease‐related knowledge. Patients also completed a demographic and clinical questionnaire. Results: A total of 203 patients were included, 62% were female, and 66% were diagnosed with ulcerative colitis; the median age was 34 years (range 18–79), and the median disease duration was four years. The median disease‐related knowledge score was 9 (range 1–20). Only 29% of the patients answered more than 50% of the questions correctly. Lower disease‐related knowledge was observed in questions related to pregnancy/fertility and surgery/complications. Patients older than 50 years, with ulcerative colitis, with disease durations less than five years and patients without histories of surgery exhibited lower disease‐related knowledge. There was no association between the knowledge scores and the educational levels. Conclusions: The patients who attended our inflammatory bowel disease programme exhibited poor disease‐related knowledge that was similar to the knowledge levels that have been observed in developed countries. It is necessary to assess patient knowledge to develop educational strategies and evaluate the influences of these strategies on patient compliance and quality of life. Relevance to clinical practice: These results will allow the inflammatory bowel disease team to develop educational programmes that account for the disease‐related knowledge of each patient. Inflammatory bowel disease nurses should evaluate their interventions to provide evidence that educating our patients contributes to improving their treatment outcomes and overall health statuses.